Serum neurofilament light chain levels in myasthenia gravis patients with and without symptoms - Lv, Jie; Liu, Ruichen; Sun, Zhan; Zhang, Jing; Zhang, Yingna; Zhao, Xue; Liu, Jing; Zhou, Xinyue; Zhang, Mengdi; Liu, Qian; Gao, Feng (Frontiers in Medicine, 2025)
This study aimed to investigate serum neurofilament light chain (sNFL) levels in patients with myasthenia gravis (MG) and explore its potential as a biomarker for disease stratification. A total of 60 MG patients and 29 normal controls (NCs) were enrolled, with no significant differences in age or gender between the two groups. MG patients were stratified by MGFA classification, QMG scores, antibody status, phenotypic subtypes, onset age, and gender. Results showed that MG patients had significantly higher sNFL levels (median: 12.7 pg./mL) compared to NCs (median: 9.1 pg./mL; p = 0.0176). Subgroup analyses revealed that sNFL levels in MGFA-II patients (median: 13.1 pg./mL) were significantly elevated compared to NCs (p = 0.0437), with no statistical difference in MGFA-I. Patients with QMG scores 7–15 (median: 13.4 pg./mL) had higher sNFL levels than those with scores 0–6 (p = 0.0207) and showed significant differences from NCs (p = 0.0023). Late-onset MG (LOMG) patients (median: 13.4 pg./mL) had higher sNFL levels than early-onset cases (p = 0.0368), and age was mildly correlated with sNFL in MG (p = 0.0477). ROC analysis showed moderate diagnostic performance of sNFL for distinguishing LOMG vs. NCs (>50 years) was 0.9464 (specificity 89.29%, sensitivity 90%), and for female MG vs. female NCs was 0.8091. In conclusion, sNFL levels are elevated in MG patients, particularly in severe and late-onset cases, suggesting its potential as a biomarker for disease stratification and severity assessment.